Development and Feasibility of BIOSTACKO, a Game-Based Biology Learning Media Integrating Religious Values for Biodiversity in Senior High School - Early Deswita Uzla; Achmad Ali Fikri (International Journal of Learning Media on Natural Science (IJLENS), 2026)
This study aimed to develop BIOSTACKO, a game-based biology learning media integrating religious values for biodiversity material in senior high school, and to determine its feasibility and practicality. The study employed a Research and Development (R&D) approach using the 4D model, which includes define, design, develop, and limited disseminate stages. The product was validated by a material expert, a media expert, and a religious expert, and its practicality was assessed through responses from one biology teacher and students in a limited classroom trial. The validation results showed that BIOSTACKO obtained scores of 97% from the material expert, 88% from the media expert, and 95% from the religious expert, indicating that the product was highly feasible. The practicality test showed scores of 98% from the teacher and 92% from students, indicating that the media was highly practical for classroom use. These findings suggest that BIOSTACKO is a feasible and practical alternative learning media for biodiversity material that may support student engagement, conceptual understanding, and the integration of religious values in biology learning.